Acoustic Radiation Force Impulse (ARFI) and High-Frequency Ultrasound of the Liver Surface for the Diagnosis of Compensated Liver Cirrhosis - Pfeifer, L.; Goertz, R. S.; Sturm, J.; Wachter, D.; Riener, M. O.; Schwitulla, J.; Bernatik, T.; Neurath, M. F.; Strobel, D. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: To evaluate the diagnostic value of acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface, using histology as a gold standard for the diagnosis of compensated liver cirrhosis.Materials and Methods: 73 patients without ascites undergoing liver biopsy were included in the study. The left and right liver lobes were examined with ARFI and high-frequency ultrasound. Liver surface irregularity was quantified using image analysis software to calculate the difference between the real surface and the approximated physiological surface through a 20 mm standardized line.Results: There is a significant difference between cirrhotic and non-cirrhotic patients for both quantified liver surface (QLS) and ARFI (p < 0.001). The mean values for QLS of the left lobe were 0.71 ± 0.24 mm and 1.17 ± 0.80 mm, of the right lobe 0.56 ± 0.26 mm and 0.87 ± 0.26 mm for non-cirrhotic and cirrhotic patients, respectively. The mean values of ARFI measurements of the left lobe were 2.04 ± 0.76 m/s and 2.85 ± 0.81 m/s, of the right lobe 1.65 ± 0.61 m/s and 3.02 ± 0.77 m/s for non-cirrhotic and cirrhotic patients, respectively. Diagnostic accuracy (AUROC) was 0.78/0.80 for QLS and 0.77/0.91 for ARFI of the left/right lobe, respectively. ARFI of the right lobe is significantly better than ARFI of the left (p = 0.023) or QLS of the left (p = 0.025)/right (p = 0.046) lobe of the liver.Conclusion: Assessment of liver surface irregularity by high-frequency ultrasound (QLS) is a useful diagnostic test for the assessment of compensated liver cirrhosis. ARFI of the right liver lobe is significantly better than high-frequency ultrasound (QLS of the left/right lobe of the liver) and ARFI of the left lobe of the liver.
Keywords: cirrhosis; high-frequency ultrasound; elastometry; liver surface; ARFI